Stable Latent HIV Infection and Low-level Viremia Despite Treatment With the Broadly Neutralizing Antibody VRC07-523LS and the Latency Reversal Agent Vorinostat. (25th September 2021) - Gay, Cynthia L; James, Katherine S; Tuyishime, Marina; Falcinelli, Shane D; Joseph, Sarah B; Moeser, Matthew J; Allard, Brigitte; Kirchherr, Jennifer L; Clohosey, Matthew; Raines, Samuel L M; Montefiori, David C; Shen, Xiaoying; et al.
Abstract: We tested the combination of a broadly neutralizing HIV antibody with the latency reversal agent vorinostat (VOR). Eight participants received 2 month-long cycles of VRC07-523LS with VOR. Low-level viremia, resting CD4+ T-cell–associated HIV RNA (rca-RNA) was measured, and intact proviral DNA assay (IPDA) and quantitative viral outgrowth assay (QVOA) were performed at baseline and posttreatment. In 3 participants, IPDA and QVOA declines were accompanied by significant declines of rca-RNA. However, no IPDA or QVOA declines clearly exceeded assay variance or natural decay. Increased resistance to VRC07-523LS was not observed. This combination therapy did not reduce viremia or the HIV reservoir. Clinical Trials Registration . NCT03803605.